WHATSAPP VS PUSH NOTIFICATIONS: UNLOCKING E-GROCERY AFFILIATE PERFORMANCE WITH OPTIMAL STRATEGIC TIMING - Laksmi, Indriana; Sumarwan, Ujang; Munandar, Jono M (LPPM Universitas Jambi, 2026)
This study aims to examine the effect of communication media type and delivery timing on user engagement and behavioral conversion within an e-grocery affiliate program. The research identifies a critical gap in existing literature regarding the comparative effectiveness of personalized external triggers (WhatsApp Blast) versus in-app alerts (Push Notifications) for the domestic housewife segment. The study was conducted using a sample of 500 active female consumers in the